Improving the Patient Handoff Process in the Intensive Care Unit: Keys to Reducing Errors and Improving Outcomes - Colvin, Mai O.; Eisen, Lewis A.; Gong, Michelle Ng (Seminars in Respiratory and Critical Care Medicine, 2016)
Patient handoffs are highly variable and error prone. They have been recognized as a major health care challenge. Patients in the intensive care unit are particularly vulnerable due to their complex clinical history and the critical nature of their condition. Given a general movement from traditional long call to shift schedules, the number of patient handoffs will likely continue to increase. Optimization of the handoff process has become even more critical to ensure patient safety. In this review, we reflect on the importance of the handoff process, review common errors, identify barriers and challenges, and propose different methods to improving the handoff process. The purpose of this article is to examine the overall scope of the problem; provide the most up-to-date evidence on the handoff process; and identify ways to perform handoffs in an accurate, safe, and efficient manner to provide high-quality patient care. The direction of future research is also proposed.
Keywords: handoff; handover; critical care; patient safety; communication; continuity of care; medical error; quality improvement